Los Colegios Rurales Agrupados, primer paso al mundo docente - Ana Ponce de León Elizondo; Enrique Bravo Sáinz; Teresa Torroba Santa María (Universidad de La Rioja, 2013)
The steadfast search for improving the quality of the education in the rural areas has led to the creation of the Rural Assembled Centres -CRAs- in recent years, practically all over the Spanish territory. The special conditions of the rural areas demand the adaptation of the educative system to their peculiarities, as a result of it the internal educative organization is different to the other schools´. This paper studies and analyses the conditions of their creation and explains the organization and functioning of these centres, starting from the current legal framework, which support them, to pay attention on the development of a Rural Assembled Centre in the Autonomic Community of La Rioja. We also present, in this paper, some appraisals in relation to this kind of schools, once there have passed several years since their creation. This study intends to be useful for the Initial Teacher Training, since the first appointment as a teacher will probably be a Rural Assembled Centre -CRA- if the would-be teacher professionally chooses to enter into the State School System.